2022
DOI: 10.1111/acer.14853
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐related differences in pattern of ethanol drinking under the intermittent‐access model and its impact on exploratory and anxiety‐like behavior in Long‐Evans rats

Abstract: Background While men in the United States consume more alcohol than women, rates of drinking are converging. Nevertheless, females remain underrepresented in preclinical alcohol research. Here, we examined rats' sex‐related differences in patterns of ethanol (EtOH) drinking and the effects of this drinking on exploratory and anxiety‐like behavior. Methods Adult male and female Long‐Evans rats were given 20% ethanol under the intermittent‐access two‐bottle‐choice paradigm. Their intake was measured daily for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…These findings are in mostly line with previous research showing sex differences in drug use, particularly stimulant drugs (Carroll and Anker 2010). Females have higher alcohol preference ratios (alcohol/total fluid) in free choice paradigms (Lancaster and Spiegel 1992;Priddy et al 2017;Pirino et al 2022), wider distribution of alcohol consumption across the day (Juárez and Tomasi 1999), and higher intake of alcohol per body weight (Lancaster et al 1996;Klein 2015). Other studies show that female mice and rats acquire ethanol self-administration faster (Melón et al 2013;Moore and Lynch 2015), show less withdrawal symptoms (Varlinskaya and Spear 2004), and have a lower response to pharmacological treatments for AUD (Moore and Lynch 2015) compared to males.…”
Section: Males and Female Rats React Differently To Ethanolsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are in mostly line with previous research showing sex differences in drug use, particularly stimulant drugs (Carroll and Anker 2010). Females have higher alcohol preference ratios (alcohol/total fluid) in free choice paradigms (Lancaster and Spiegel 1992;Priddy et al 2017;Pirino et al 2022), wider distribution of alcohol consumption across the day (Juárez and Tomasi 1999), and higher intake of alcohol per body weight (Lancaster et al 1996;Klein 2015). Other studies show that female mice and rats acquire ethanol self-administration faster (Melón et al 2013;Moore and Lynch 2015), show less withdrawal symptoms (Varlinskaya and Spear 2004), and have a lower response to pharmacological treatments for AUD (Moore and Lynch 2015) compared to males.…”
Section: Males and Female Rats React Differently To Ethanolsupporting
confidence: 90%
“…Female animals performed better than males. Bars denote standard error same ethanol dose injection (Mankes et al 1991) and similar blood ethanol concentrations for greater ethanol intake (Pirino et al 2022) which may be explained by the higher hepatic alcohol dehydrogenase activity in females compared to male rats (Quintanilla et al 2007). However, it is currently unclear whether the enhanced drinking in females is related to the reduced side effect potential in these animals and why we see no differences in alcohol preference in the 24-h drinking sessions.…”
Section: Males and Female Rats React Differently To Ethanolmentioning
confidence: 99%
“…Notably, there were no group effects of EtOH drinking on pain sensitivity or affective behavior. While previous studies have seen effects of EtOH on pain sensitivity and affect(Quadir et al, 2021b) (Gong et al, 2017; Overstreet et al, 2005; Van Skike et al, 2015; Xu et al, 2021), others studies have not (Bloch et al, 2020; McNamara and Ito, 2021; Pirino et al, 2022) One potential explanation is that rats in the present study only drank for 3-4 weeks before behavioral testing and thus did not consume enough EtOH to produce behavioral deficits. Studies in Wistar rats report escalated intake after ∼20 EtOH drinking sessions(Carnicella et al, 2009; George et al, 2012; Kimbrough et al, 2017); rats in this study only drank for 16 sessions.…”
Section: Discussionmentioning
confidence: 57%
“…Females also consumed more ethanol than males in both the F1 and F2. This is not surprising as several previous studies has shown that drinking behaviour shows sex-based differences with females consuming greater amounts of ethanol per bodyweight (Hussain et al, 2022;Lancaster et al, 1996), showing higher preferences for ethanol than males (Hussain et al, 2022;Lancaster & Spiegel, 1992;Pirino et al, 2022;Priddy et al, 2017), developing drinking behaviour faster (Melón et al, 2013;Moore, C. F. & Lynch, 2015) and showing different drinking patterns across a session (Juárez & De Tomasi, 1999).…”
Section: Ethanol Drinkingmentioning
confidence: 52%
“…These baseline differences must be considered when looking at performance under ethanol because while we see similar performances under the influence of ethanol between the ND1 males and females, the females show a greater drop from baseline performance. Motor impairment due to ethanol has been reported to affect sexes differently (Hussain et al, 2022;Vetter-O'Hagen et al, 2009) This has been attributed to differences in alcohol metabolism with studies showing lower blood ethanol levels for the same ethanol dose (Mankes et al, 1991) and similar blood ethanol concentrations for greater ethanol intake (Pirino et al, 2022)in females compared to male rats.…”
Section: Locomotor Activity and Rotarodmentioning
confidence: 99%